Traits underlying community consequences of plant intra-specific diversity. - Luis Abdala-Roberts; Riley Pratt; Jessica D Pratt; Kailen A Mooney (PLoS ONE, 2017)
A plant's performance and interactions with other trophic levels are recorgnized to be contingent upon plant diversity and underlying associational dynamics, but far less is known about the plant traits driving such phenomena. We manipulated diversity in plant traits using pairs of plant and a substitutive design to elucidate the mechanisms underlying diversity effects operating at a fine spatial scale. Specifically, we measured the effects of diversity in sex (sexual monocultures vs. male and female genotypes together) and growth rate (growth rate monocultures vs. fast- and slow-growing genotypes together) on growth of the shrub Baccharis salicifolia and on above- and belowground consumers associated with this plant. We compared effects on associate abundance (# associates per plant) vs. density (# associates per kg plant biomass) to elucidate the mechanisms underlying diversity effects; effects on abundance but not density suggest diversity effects are mediated by resource abundance (i.e. plant biomass) alone, whereas effects on density suggest diversity effects are mediated by plant-based heterogeneity or quality. Sexual diversity increased root growth but reduced the density (but not abundance) of the dietary generalist aphid Aphis gossypii and its associated aphid-tending ants, suggesting sex mixtures were of lower quality to this herbivore (e.g. via reduced plant quality), and that this effect indirectly influenced ants. Sexual diversity had no effect on the abundance or density of parasitoids attacking A. gossypii, the dietary specialist aphid Uroleucon macolai, or mycorrhizae. In contrast, growth rate diversity did not influence plant growth or any associates except for the dietary specialist aphid U. macolai, which increased in both abundance and density at high diversity, suggesting growth rate mixtures were of higher quality to this herbivore. These results highlight that plant associational and diversity effects on consumers are contingent upon the source of plant trait variation, and that the nature of such dynamics may vary both within and among trophic levels.